Assessing Uterine Rupture: A Bibliometric Analysis of a Critical Emergency for Women’s Health - Engin Yıldırım; Habibe Selmin Özensoy (Global Emergency and Critical Care)
Objective: This study aimed to provide a comprehensive bibliometric analysis of academic literature related to uterine rupture, highlighting trends, publication productivity, and key contributors in this critical area of women’s health. Materials and Methods: A comprehensive analysis of the Web of Science (WoS) database was conducted, encompassing articles published from 1980 to 2023. Keywords “uterine rupture” and “uterus rupture” were utilized. Data visualization was facilitated using Datawrapper, while VosViewer 2019 was used to analyze coauthorship and citation networks. Results: A total of 5.828 publications were identified, of which 5.745 were analyzed after excluding studies from 2024. The United States, England, and France emerged as the top contributing countries. The American Journal of Obstetrics and Gynecology was the leading journal. The publication rate has steadily increased, peaking in 2020. The most cited article, “risk of uterine rupture during labor among women with a prior cesarean delivery” reflects ongoing concerns in obstetric care. Collaborations between researchers and institutions are evident, with significant networks formed around key authors. Conclusion: Uterine rupture remains a pressing clinical issue, increasingly prevalent due to rising cesarean rates. Emergency physicians and obstetricians should understand the risk factors and diagnostics. Continued growth in research publications is anticipated, with a focus on multidisciplinary approaches to enhance understanding and management strategies for uterine rupture.